Lemahnya Pengetahuan dan Penerapan Ilmu Tentang Bahayanya Syirik Bagi Kehidupan - Fatuhrachman Saleh; Fauzan Mubarokh; Muhammad nabil ayussy; Wahyu rayan kenedi; Wismanto Wismanto (STIKes Ibnu Sina Ajibarang, 2024)
Shirk, in a religious context, refers to actions or beliefs that involve allying with or attributing divine attributes to other than Allah, either explicitly or implicitly. This term has great significance in various religions, especially in the Islamic religion, and also in several other religious traditions. Shirk is seen as a major sin and one of the main violations of the monotheistic belief that underlies many religious belief systems. Shirk includes various practices or beliefs that have the potential to threaten human well-being from a religious perspective. Although diverse in form, shirk has the potential for significant negative impacts on individuals and society at large. Therefore, a deep understanding of shirk and awareness of its dangers is very important to promote correct understanding of religion and support peace, harmony and prosperity in society.